2017
DOI: 10.1038/s41598-017-09208-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prototyping of Polymeric Nanopillars by 3D Direct Laser Writing for Controlling Cell Behavior

Abstract: Mammalian cells have been widely shown to respond to nano- and microtopography that mimics the extracellular matrix. Synthetic nano- and micron-sized structures are therefore of great interest in the field of tissue engineering, where polymers are particularly attractive due to excellent biocompatibility and versatile fabrication methods. Ordered arrays of polymeric pillars provide a controlled topographical environment to study and manipulate cells, but processing methods are typically either optimized for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The model also suggests that membrane wrapping around the nanowire is not normally energetically favorable and requires external force. They were able to verify their model against literature and experimental data, also observing an intermediate settling between the fully deformed and on‐top regimes.…”
Section: Modeling the Cell–nanostructure Interfacementioning
confidence: 58%
See 2 more Smart Citations
“…The model also suggests that membrane wrapping around the nanowire is not normally energetically favorable and requires external force. They were able to verify their model against literature and experimental data, also observing an intermediate settling between the fully deformed and on‐top regimes.…”
Section: Modeling the Cell–nanostructure Interfacementioning
confidence: 58%
“…The result of Xie et al highlighting the lack of spontaneous penetration provided an assumption (exploited in later models) that to effectively understand cell behavior, the balance of free energy of the membrane (rather than gravitational force) should be considered. Martinez and co‐workers have extensively studied geometry‐dependent cell response both experimentally and theoretically . Their model considers the cell as a soft‐shelled droplet, and defines the free energy of the cell–substrate interaction as the sum of the cell–substrate adhesion, the change in surface tension caused by an increase in cell surface area, and the change in elastic energy caused by bending the membrane .…”
Section: Modeling the Cell–nanostructure Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, N. Mnson et al demonstrated the fabrication of polymer nanopillars (NP) using 3D direct laser writing (3D DLW). It have been shown that polymer NPs generally provided a biocompatible environment for cell adhesion and sustained cell growth, therefore, synthetic nano-and micro-sized structures were of great importance in the field of tissue engineering [152]. Scanning electron microscopy (SEM) images of an array of 3 µm long NPs of all pitches tested in the cell studies described were shown in Figure 17b-g.…”
Section: D/3d Polymer Structures By Direct Laser Writing (Dlw)mentioning
confidence: 99%
“…Micro-and nanostructured surfaces can be fabricated using various lithographic techniques. Fabrication approaches such as mask-based photolithography 22 and mask-less photolithography 23,24 are frequently applied, but structure resolution are for both techniques limited by the optical diffraction limit. Other approaches such as dip pen lithography, 25 nano-sphere lithography, 26 block-copolymer lithography 27 and other similar approaches 28 are able to perform structuring with sub-100 nm resolution, but have a limited throughput.…”
Section: Introductionmentioning
confidence: 99%